Comparison of Dental Students' Self‐Directed, Faculty, and Software‐Based Assessments of Dental Anatomy Wax‐Ups: A Retrospective Study. Issue 12 (1st December 2015) - Garrett, Pauline H.; Faraone, Karen L.; Patzelt, Sebastian B.M.; Keaser, Michael L.
Abstract : Little is known about self‐directed and self‐reflective assessment in preclinical dental curricula. The aim of this study was to evaluate a visual dental anatomy teaching tool to train dental students to self‐assess their dental anatomy wax carving practical examinations. The students self‐assessed two waxing practical examinations (tooth #8 and tooth #19) using high‐quality digital images in an assessment tool incorporated into a digital testing program. Student self‐assessments were compared to the faculty evaluations and the results of a software‐based evaluation tool (E4D Compare). Out of a total 130 first‐year dental students at one U.S. dental school, wax‐ups from 57 participants were available for this study. The assessment data were submitted to statistical analyses (p<0.05). For tooth #8, the student self‐assessments were significantly different from the faculty and software assessments at a 400 micrometer level of tolerance (p=0.036), whereas the faculty assessment was not significantly different from the software assessment at a 300 micrometer level of tolerance (p=0.69). The evaluation of tooth #19 resulted in no significant differences between faculty members (p=0.94) or students (p=0.21) and the software at a level of tolerance of 400 micrometers. This study indicates that students can learn to self‐assess their work using self‐reflection in conjunction with faculty guidance and that it may be possible to use software‐based evaluation tools to assist in faculty calibration and as objective grading tools.